Pengelolaan Pembelajaran Ipa Di SD NegeriPajang IV Surakarta - Askundari, Tiwi, Dr. Sofyan Anif, M.Si, Dr. Wafrotur Rohmah ,M.M (2017)
The purpose of this study was to describe (1) the learning plan IPA; (2) the organization of science teaching; (3) The implementation of learning science; and (4) the assessment and follow-up science teaching. The research is a qualitative research with ethnographic research design. The research location is on SD Negeri Surakarta Pajang IV. Mechanical pengumplan data using in-depth interviews, documentation, and observation. Analysis of the data using three stages: data reduction, data presentation, and drawing conclusions with verification. The results of this study indicate that the planning of science learning is learning scenarios prepared by teachers who already have an understanding of the purpose of education, master of teaching materials, understand the theory of education in addition to the theory of teaching, understand the principles of teaching, understand the theories of learning, understanding the methods of teaching, understand the models of teaching, understand the principles of evaluation, and understand the steps to create lesson plans. Compiled by the working group of teachers and developed by teachers each with reference to the curriculum and syllabus in force nationally. Organizing learning science learning organization, consisting of three (3) stages: stage before teaching, teaching stage, and the stage after the teaching. Implementation of learning is the implementation of the RPP. Implemented by classroom teachers include preliminary activities, core activities, and closing activity. Science teaching methods used by teachers and students adjusted to the characteristics of the subjects, which may include the exploration, elaboration, and confirmation. The activities cover the activities of teachers to summarize or make inferences lessons with students. The model used in the evaluation of science teaching is done through summative and formative evaluation, the type of assessment used by teachers are: performance assessment, a written assessment, project assessment, product assessment, penilaain portfolio, and selfassessment. Assessment is done in writing and orally. About the tests used by teachers in a written assessment test has not been performed validity. Keywords: planning, organizing, implementation, assessment, and IPA